'A design method for the dilution zones of gas turbine combustion chambers' - Lefebvre, Arthur H.; Norster, E. R. (College of Aeronautics, 1966)
Introduction and Summary Perhaps the most important and, at the same time, most difficult Problem in the design and development of gas turbine combustion chambers, is that of achieving a satisfactory and consistent distribution of temperature in the efflux gases discharging into the turbine. In the past, experience has played a major role in the determination of dilution-zone geometry, and trial and error methods have of necessity been employed in developing the temperature-traverse quality of individual combustor designs to a satisfactory standard. Experimental investigations into dilution-zone performance carried out on actual chambers have led to useful empirical-design data, but very often it has proved difficult or impossible to distinguish the separate influences of all the variables involved. Thus although it is now generally accepted that a satisfactory temperature profile is dependent upon adequate penetration of the dilution jets, coupled with the correct number of jets to form sufficient localized mixing regions, the manner in which the total dilution-hole area is Utilized in terms of number and size of holes is still largely a matter of experience. Unfortunately, more basic studies of jet mixing do not usually yield results that can readily be expressed in the parameters which are most familiar to those concerned with combustion-chamber design. However, some of these investigations can provide a useful guide to the relationships involved. One such investigation resulted in the accumulation of a large amount of data on the mixing of cold jets when injected into hot streams under conditions where the temperature and velocity of the hot and cold streams, the injection-hole diameter, the angle of injection, and the mixing length could be accurately controlled and varied over a wide range. These data are used here, firstly to demonstrate a logical method of dilution zone design and, secondly, to provide quantitative data on the rate of exchange between temperature traverse quality and the relevant design parameters such as dilution zone length, dilution hole diameter and pressure loss factor. The effects of chamber inlet velocity and inlet velocity profile are also examined. Finally, it is proposed that the aerodynamic performance and stability of a combustion chamber may, for most practical purposes, be adequately described in terms of a parameter p which is the ratio of the flametube pressure loss to the overall pressure loss. Evidence is presented in